Identifikasi Pertumbuhan Urban Heat Island secara Spasial-Temporal di Kota Palangka Raya Menggunakan Penginderaan Jauh dan Sistem Informasi Geografis - Afrilyani Kontryana; Abdul Wahid Hasyim; Amin Setyo Leksono (Jurnal Serambi Engineering, 2021)
Developments in the city of Palangka Raya y giving different temperature between urban and sub-urban. Phenomenon that  cities have warmer temperatures than sub-urban and rural areas called Urban Heat Island (UHI). This study aims to find out about the development of the UHI phenomenon in the city of Palangka Raya  from 2000  to 2018 using remote sensing and geographical system. Based on the analysis of the TIR band landsat 7,  in Kota Palangka Raya since 2000 has been UHI phenomenon, where high Land Surface Temperature (LST) was found dominantly in urban areas  compared to sub-urban areas . In 2018, as Palangka Raya city  had developed, based on the result of TIR band Landsat 8, the distribution of high LST not only found in the urban area, but in the sub-urban zone, especially at  Menteng Urban Village and Panarung Urban Village. The development of UHI in Palangka Raya city over eighteen years (2000-2018) show  in the sub-urban area  experienced changes of UHIindex’s area more dynamic than the urban area. Urban development causing to conversion of  vegetated land into impervious land,  which greatly affects the energy balance. The increase in impervious areas causes more solar radiation  that reaches the surfaces of the earth   more absorbing and it is converted into sensible thermal  energy which increases the surface temperature.